Evaluation of the Accelerate Pheno™ System for the Identification and Antimicrobial Susceptibilty Testing of Gram-negative Bacteria, Compared with Conventional Laboratory Testing. (4th October 2017) - Roulston, Kerry; Gorton, Rebecca; Kazantzaki, Ekaterini; Rebec, Monica; Hopkins, Susan; Satta, Giovanni; Mack, Damien
Abstract: Background: The current standard technique for diagnosis of bloodstream infection (BSI) is through the detection of micro-organisms using automated blood culture systems and subsequent phenotypic antimicrobial susceptibilty testing (AST) techniques that require 24–48 hours to generate results. The aim of this study was to evaluate the Accelerate Pheno™ system (AXDX), which utilises fluorescent in situ hybridization and morphokinetic cellular analysis to identify bacteria from positive blood cultures and perform AST in less than 7 hours. Methods: The Accelerate PhenoTest™ BC kit was used to test 15 gram-negative isolates with a range of AST profiles, from simulated blood cultures. Isolates included 10 target organisms; Escherichia coli ( n = 2), Enterobacter sp. ( n = 2), Klebsiella sp., Proteus sp., Citrobacter sp., Pseudomonas aeruginosa, Acinetobacter baumannii, Serratia marcescens and 5 non-target organisms. AXDX results were compared with MALDI-ToF MS identification and BD Phoenix™ automated AST results. To evaluate the reproducibility of AXDX analysis, all isolates were tested at two different sites, six in duplicate. Results: A total of 37 tests were performed. AXDX correctly identified 90% (9/10) of the target organisms, and correctly identified 100% (5/5) of non-target organisms as such. One isolate of Citrobacter sp. was initially misidentified as Enterobacter sp. but was correctly identified twice on repeat testing. The AST results demonstrated 93% (244/262) essential agreement (MIC within <1 dilution) and 90% (237/262) categorical agreement (same S/I/R interpretation) compared with conventional laboratory methods. For AST results, between-site reproducibility (MIC within <1 dilution) was 97%. Conclusion: The Accelerate PhenoTest™ BC kit can provide rapid identification alongside phenotypic AST results direct from positive blood cultures. In this study, the assay demonstrated high reproducibility and good correlation with conventional laboratory methods. By reducing the time to AST results the Accelerate Pheno™ system has the potential to produce actionable results for the management of BSI and enable earlier escalation or de-escalation of antibiotic therapy. This also has the potential to improve patient outcomes by reducing morbidity and mortality. Disclosures: K. Roulston, Accelerate Diagnostics: Investigator, Research support; R. Gorton, Accelerate Diagnostics: Investigator, Research support; E. Kazantzaki, Accelerate Diagnostics: Investigator, Research support; M. Rebec, Accelerate Diagnostics: Investigator, Research support; S. Hopkins, Accelerate Diagnostics: Investigator, Research support; G. Satta, Accelerate Diagnostics: Investigator, Research support; D. Mack, Accelerate Diagnostics: Investigator, Research support